2021
DOI: 10.21203/rs.3.rs-90067/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory seeds enable high structural phase purity in 2D perovskite films for high-efficiency devices

Abstract: Two-dimensional (2D) perovskites are a class of halide perovskites offering a pathway for realizing efficient and durable optoelectronic devices. However, the broad chemical phase space and lack of understanding of film formation have led to quasi-2D perovskite films with polydispersity in perovskite layer thicknesses, which have hindered devices performance and stability. Here, we demonstrate a scalable approach involving dissolution of single-phase crystalline powders with homogeneous perovskite layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Rather, DMF and FA together could act as surfactants or help the formation of an n = 3 “seed” in the precursor solution that result in large and homogeneously‐oriented domains. [ 48,50 ] The N‐H group of FA in the interlayer can form hydrogen bonds with DMF, resulting in DMF incorporation into the interlayer of an n = 3. Thus, the large, homogeneously oriented domains of the spin‐cast x FA = 0.07 film likely originate from the interactions of DMF and FA in the precursor solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, DMF and FA together could act as surfactants or help the formation of an n = 3 “seed” in the precursor solution that result in large and homogeneously‐oriented domains. [ 48,50 ] The N‐H group of FA in the interlayer can form hydrogen bonds with DMF, resulting in DMF incorporation into the interlayer of an n = 3. Thus, the large, homogeneously oriented domains of the spin‐cast x FA = 0.07 film likely originate from the interactions of DMF and FA in the precursor solution.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3,32,37,40 ] Because the orientation of the semiconducting 2D layers determines the direction of carrier transport, controlling their orientation is crucial for optoelectronic applications. [ 3,21,24,37,40,41 ] Much research has focused on overcoming these challenges, [ 30–32,34,37,42–54 ] with recent findings showing that that judicious choice of precursor salts [ 50 ] and A/A′ cations [ 52 ] can yield pure, single‐phase films of 2D phases with n > 1.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Mohite and co‐workers demonstrated a phase‐selective method involving the dissolution of phase‐pure 2D perovskite single‐crystalline powders to fabricate phase‐pure 2D perovskite thin films. [ 62 ] The authors revealed the presence of sub‐micrometer‐sized seeds in solution that preserve the memory of the dissolved single crystals; these seeds template the nucleation and growth of phase pure grains with the identical composition in the resulting 2D perovskite thin films. Solar cells fabricated with such films yielded an enhanced PCE and operational stability over solar cells based on conventional 2D perovskite films having a broad distribution of n 's, which further implies accessing phase‐pure 2D perovskite films with prescribed n 's to be an effective way to further improve device performance.…”
Section: Challenges and Strategies To Advance 2d Perovskites Solar Cells (N ≤ 5)mentioning
confidence: 99%
“…Recently, researchers have also reported phase‐pure 2D perovskites using molten butylamine acetate instead of butylamine iodide [ 61 ] or using single‐crystalline powders as precursors. [ 62 ] It will be interesting to see if this strategy works for other chemistries. By contrast, addressing the challenges at the unit‐cell level (i.e., accessing 2D perovskites with unit‐cell level donor‐acceptor heterojunctions without octahedra distortion) will likely require more effort.…”
Section: Challenges and Strategies To Advance 2d Perovskites Solar Cells (N ≤ 5)mentioning
confidence: 99%
“…Submicrometer‐sized seeds in precursor solution preserve the memory of the dissolved single crystals, templating the nucleation and growth of phase pure grains with the identical composition in the resulting 2D perovskite thin films, enabling PCEs up to 17.1%, with a high fill factor (FF) of 81.1%. [ 30 ] However, most of these methods are limited to butylammonium as a spacer and the wider applicability for aromatic spacers needs to be explored. Also, most 2D‐RPP films are fabricated in an inert glove box environment and the imposition of such strict fabrication conditions can make commercial‐scale manufacturing difficult.…”
Section: Introductionmentioning
confidence: 99%